Enhancing Basic Leadership Skills Through the IPNU-IPPNU Leadership Camp in Semarang - Taujiharrahman, Darma (Society : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to enhance the basic leadership capacity of students affiliated with IPNU-IPPNU in Semarang City through a Leadership Camp program. The activity was conducted on December 13–14, 2025, at Vilaqu Bandungan using a participatory training approach based on experiential learning. The implementation method consisted of planning, execution, and evaluation stages. The materials covered Islamic values, national awareness, organizational understanding, and basic leadership skills. The results indicate an improvement in participants’ understanding and readiness to assume leadership roles, as reflected in their active participation and appointment as organizational administrators. This program contributes to shaping young leaders who are ethical, religious, and nationally oriented.